0361 Prevalence and Predictive Factors of Sleeping Medication Use Among Students at a Canadian University. (27th April 2018) - King, E; Lane, H; Garland, S N
Abstract: Introduction: University students experience high levels of stress and sleep disturbance, increasing the likelihood of sleep-promoting substance use. Long-term use of sleeping aids can lead to chronic sleep problems and dependence. It is important to understand the factors that predict such use in order to offer prevention/intervention programs for at-risk groups. Methods: 3, 699 students aged 18–35 at Memorial University of Newfoundland were surveyed. Participants indicated whether they had used sleeping medications (over the counter and/or prescription) in the last month and completed the Insomnia Severity Index, Pittsburgh Sleep Quality Index, Hospital Anxiety and Depression Scale, and the Prescription Drug Attitudes Questionnaire. Univariate and multivariate logistic regression were used to examine the demographic and clinical factors associated with sleeping medication use. Results: 73% of participants were female and 49% aged 18–21 years. 22% reported using at least one type of sleep-promoting substance. In the multivariate model, female students were more likely than males to report using sleeping medication (AOR=1.65; 95%CI, 1.18 to 2.30; p =0.003). Students aged 24–35 were more likely than those aged 18–21 (AOR=1.95; 95%CI, 1.28 to 2.96; p =0.002) and those with poor sleep quality were more likely to use sleeping medication than those with good sleep quality (AOR=2.07; 95%CI, 1.26 to 3.41; p =0.004). Not surprisingly, insomnia symptoms was a robust predictor of sleeping medication use (Mild: AOR=2.34; 95%CI, 1.68 to 3.25; p <0.001; Moderate: AOR=3.60; 95%CI, 2.37 to 5.48; p <0.001; Severe: AOR=6.93; 95%CI, 3.12 to 15.38; p <0.001). Students with the most positive attitudes towards non-medical use of prescription drugs were more likely to use sleeping medication (AOR=2.31; 95%CI, 1.63 to 3.27; p <0.001). Conclusion: This is the first study to examine sleeping medication use among students at a Canadian university. The results indicate that almost 25% of students are using substances to help them sleep. Students who are female, over 24 years old, have insomnia or more lenient attitudes towards substance use are all more likely to use sleeping medications. These groups are targets for sleep education and stress management interventions. Support (If Any):